(untitled) - Dawson, Raymond (Oxford, 1981)
Contents: confucius and Kung Fu-tzu; Learning and teaching; ritual and music; humaneness and other virtues; gentlemen and knights; goverment and people; a confucian China...
Keywords: Confucius and confucianism,Khổng Tử và Nho giáo